(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Community participation in sustainable development projects is minimal or lacking in the natural protected areas (NPA) of Central America. Fifteen years after the Mesoamerican Reef System was implemented as an international conservation strategy, a study was done to determine local population interest in reef conservation in San Miguel de Cozumel, Mexico, and West End Village, Honduras. An evaluation was also done of coral health in nearby, heavily used reefs. Lack of community participation is linked to low levels of information, education and training, although 90% of interviewees agreed to participate in a contingent proposal involving financing of coral reef conservation activities. Participants exhibited a willingness-to-pay an average of 10% of income spent on basic food needs or the national minimum wage. Their willingness stemmed from the use value of the reefs as a tourist attraction and from their being a primary income source.Among non-use values, ensuring the well-being of their children (i.e. legacy value) was the most frequently stated followed by conserving reefs because they are a natural system (i.e. existence value). The reef coral health indicated some degree of reef deterioration compared to indicator values for the Mesoamerican Reef System. Greater community participation in NPA management and administration will require NPA authorities to develop tools for community interaction and to prove the effectiveness of their actions.